Internalisasi Nilai-nilai Karakter Peserta Didik dalam Pembelajaran Tahsin dan Tahfidzul Qur’an di SMA Darun Nasya Kabupaten Bandung Barat - Haris Fahrizal; Muhammad Hijrah M Saway (MANAZHIM, 2021)
Al-Qur'an as a holy book has an important role in the hearts of Muslims. A Muslim has an obligation to improve reading (Tahsin) and practice the messages contained. The Tahsin and Tahfidz learning programs which are currently widespread in schools and Islamic boarding schools foster a spirit of learning among the people. In particular, it motivates parents to send their children to schools that have tahfidz programs. with the hope that the Tahsin and Tahfidz programs have a positive influence on the growth and development of students. This study aims to identify how the implementation of the tahsin and tahfidz programs at SMA Darun Nasya with the hope of providing information on the internalization of character values. This type of research is field research with data collection techniques in the form of interviews, observations, and documentation. The results showed that there was a pattern of behavior change in students after participating in the tahsin and tahfidz learning programs.